2022
DOI: 10.3389/fped.2022.1020059
|View full text |Cite
|
Sign up to set email alerts
|

Patient demographics and characteristics from an ambispective, observational study of patients with duchenne muscular dystrophy in Saudi Arabia

Abstract: Duchenne muscular dystrophy (DMD) is a rare neuromuscular disorder that is characterized by progressive muscle weakness, resulting in disability and premature death. Onset of symptoms typically occurs at 2–3 years of age, and disease progression is managed through treatment with corticosteroids. The aim of this interim analysis is to increase disease awareness and improve patient management in Saudi Arabia (SA) through the use of data from an ongoing ambispective, observational, multicenter study evaluating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nineteen studies that were not relevant to the study topic were excluded. Out of the studies related to DMD/BMD in Saudi Arabia, 4 studies reported the pathogenic variants of DMD/BMD among Saudi patients ( Table 1 ), and one described the demographics and characteristics of DMD patients in the same country ( 42 ). One study discussed the management approaches of DMD during the Coronavirus disease 2019 pandemic ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies that were not relevant to the study topic were excluded. Out of the studies related to DMD/BMD in Saudi Arabia, 4 studies reported the pathogenic variants of DMD/BMD among Saudi patients ( Table 1 ), and one described the demographics and characteristics of DMD patients in the same country ( 42 ). One study discussed the management approaches of DMD during the Coronavirus disease 2019 pandemic ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis process starts with determining the creatinine kinase (CK) level as well as concentrations of other serum enzymes, such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST) ( 40 ). Genetic testing is the first confirmatory test for the diagnosis ( 42 ). Finally, muscle biopsies for dystrophin staining are recommended for further confirmation for those with clinically compatible dystrophinopathy but with negative genetic findings ( 11 , 12 , 43 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the survival analysis for the follow-up evaluation of the patients revealed that, with the progression of the disease, the patients in Group 1 were more prone to becoming wheelchairbound at a younger age compared to those in Group 2 (p = 0.004), as depicted in Table 3 and Figure 4. The reported data on the age of wheelchair dependency in DMD patients of different populations are as follows: in India, the age is 10.4 years [18] and 13 years [34]; in Iran, the age is 10.9 years [35]; in Saudi Arabia, the age is 10.1 years [36]; in the Netherlands, the age is 9.7 years [37]; and in the UK, according to the North Star database and other related studies, the age is 13 years [10,38]. The variability observed in the age at which individuals become dependent on wheelchairs in different populations can potentially be attributed to regional disparities in patient management, healthcare resources, the socioeconomic background of the patients, genetic factors, and the influence of disease modifier genes specific to certain populations [30,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%